Clinical value of folate receptor-positive circulating tumor cells in patients with esophageal squamous cell carcinomas: a retrospective study - Qiang Zhou; Qiao He; Wenwu He; Chenghao Wang; Guangyuan Liu; Kangning Wang; Haojun Li; Jialong Li; Wenguang Xiao; Qiang Fang; Lin Peng; Yongtao Han; et al. (BMC Cancer, 2023)
Abstract Background The aim of the study is to explore the role of preoperative folate receptor-positive circulating tumor cell (FR+CTC) levels in predicting disease-free survival (DFS) and overall survival (OS) in patients with esophageal squamous cell carcinomas (ESCC). Methods Three ml blood samples were prospectively drawn from ESCC patients, and ligand-targeted polymerase chain reaction (LT-PCR) was used for the quantification of FR+CTCs. Other serum indicators were measured by traditional methods. Clinicopathological characteristics were obtained from the hospital medical record system, DFS and OS data were obtained by follow-up. The correlation between clinico-pathological characteristics, DFS, and OS and FR+CTCs were analyzed, respectively. Risk factors potentially affecting DFS and OS were explored by Cox regression analysis. Results there were no significant correlations between FR+CTCs and patient age, sex, albumin, pre-albumin, C-reactive protein (CRP), ferritin and CRP/Albumin ratio, tumor size, grade of differentiation, lymph node metastasis, TNM stage, perineural invasion/vessel invasion (all P > 0.05). Nevertheless, preoperative FR+CTCs were an independent prognostic factor for DFS (HR 2.7; 95% CI 1.31-, P = 0.007) and OS (HR 3.37; 95% CI 1.06-, P = 0.04). DFS was significantly shorter for patients with post-operative FR+CTCs ≥ 17.42 FU/3ml compared with patients < 17.42 FU/3ml (P = 0.0012). For OS, it was shorter for patients with FR+CTCs ≥ 17.42 FU/3ml compared with patients < 17.42 FU/3ml, however, the difference did not reach statistical significance (P = 0.51). Conclusions ESCC patients with high FR+CTCs tend to have a worse prognosis. FR+CTCs may monitor the recurrence of cancers in time, accurately assess patient prognosis, and guide clinical decision-making. Trial registration The study was approved by the Sichuan Cancer Hospital & Institute Ethics Committee (No. SCCHEC-02-2022-050).